Further Studies of Bolivian Crocidolite –Part IV: Fibre Width, Fibre Drift and their relation to Mesothelioma Induction: Preliminary Findings - Edward B Ilgren; Drew R Van Orden; Richard J Lee; Yumi M Kamiya; John Anthony Hoskins (Epidemiology, Biostatistics and Public Health)
Background The hypothesis that fibre width is a major determinant of mesothelioma induction has been examined by comparative studies of two crocidolites from different sources. Fine fibres fromCapesouthAfricaand the thicker fibre found and used similarly inBolivia.   It is well established that ‘thin’ fibre crocidolite fromCapeSouth Africais extremely mesotheliomagenic. Bolivian crocidolite has a much wider width distribution and relatively little mesothelioma inducing potential.   Methods We analysed the mesothelioma demography inBoliviawhere local crocidolite has been used for decades This was compared with the mesothelioma demography in theItalianCityof Casale Monteferrato whereCapecrocidolite was processed for many decades in the Eternit Asbestos Cement plant producing numerous cases of mesothelioma. We also conducted a limited downwind study from the fiberizing part of the historical operating plant where products containing Bolivian crocidolite were made for sale and use inCochabamba.   Results The demographic study confirmed the absence of a significant mesothelioma excess inBolivia. Despite the extremely high fibre concentrations measured in the plant, no significant fibre levels were detected 100 meters away.   Conclusion These preliminary findings undermine claims such as those made at Casale that crocidolite fibre can drift up to 15 km and remain airborne in quantities sufficient to contribute significantly to mesothelioma induction.   We propose the difference in thickness and the attendant reduction in the percentage ofStantonfibres provides an explanation for the difference in mesothelioma patterns found in each city.